Compare the Effectiveness of Systematic Steroids Verses Nebulizer in Pediatric Patients of Acute Exacerbation of Asthma - Mohammad Hussain, Mohammad Iqbal, Saima Rayaz, Attaullah Bizenjo, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare efficacy of the nebulizer with systematic steroids in acute exacerbation of asthma patients. Study design: Prospective study Place and duration of study: Department of Pediatric Medicine, Sandeman Provincial Hospital, Quetta from 1st February 2022 to 31st July 2022. Methodology: One hundred patients with acute exacerbation of asthma and age of 1-10 years were included. Patients were divided into two groups where Group A was given flunisolide nebulization and comprised of 50 cases. The group B was given systematic steroid budesonide. The post outcomes of treatment were noted after two weeks. Results: The mean age in group A and B as 5.8±7.45 and 5.6±7.25years respectively. More boys were presented with acute exacerbation of asthma with a percentage of 66% and 68% in group A and B than girls as 34% and 32% respectively. The duration of asthma in Group A was found to be mean 3.5±6.60 years while in group B it was 4.2±4.20 years post treatment. Hospitalization was also observed at a significant higher rate in group B than Group A. Conclusion: The nebulizer has a better efficacy than systematic steroids in acute exacerbation of asthma. Keywords: Acute exacerbation, Asthma, Pediatrics, Efficacy